The genetic basis for most patients with pustular skin disease remains elusive. (22nd January 2018) - Mössner, R.; Wilsmann‐Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J.C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K.‐P.; et al.
Summary: Background: Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause or contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP). Objectives: To better understand the disease relevance of these genes, we screened our cohorts of patients with pustular skin diseases [primarily GPP and palmoplantar pustular psoriasis (PPP)] for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN . Methods: Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients – 61 with GPP, two with acute generalized exanthematous pustulosis and four with acrodermatitis continua of Hallopeau. We screened IL36RN and AP1S3 for intragenic copy‐number variants and 258 patients with PPP for coding changes in AP1S3 . Eleven heterozygous IL36RN mutations carriers were analysed for a second noncoding IL36RN mutation. Genotype–phenotype correlations in carriers/noncarriers of IL36RN mutations were assessed within the GPP cohort. Results: The majority of patients (GPP, 64%) did not carry rare variants in any of the three genes. Biallelic and monoallelic IL36RN mutations were identified in 15 and five patients with GPP, respectively. Noncoding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype–phenotype correlation observed for IL36RN mutation carriers was early age at disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutation carriers. Conclusions: The identification of IL36RN mutation carriers harbouring additional rare variants in CARD14 or AP1S3 indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest that, in heterozygous IL36RN mutation carriers, there are additional disease‐causing genetic factors outside IL36RN . Abstract : What's already known about this topic? The genes IL36RN, CARD14 and AP1S3 have been implicated in pustular skin disease with IL36RN having a major role. Most studies have analysed variants in different genes separately. Significant subsets of patients with a pustular skin disease carry a single heterozygous mutation in IL36RN, leaving unanswered whether and how the variant is disease‐contributing. What does this study add? Intragenic copy‐number variants or noncoding mutations in carriers of single IL36RN mutations were not found. In total, 15% of patients with generalized pustular psoriasis (GPP) with IL36RN mutations carried variants in CARD14 or AP1S3, providing evidence for a complex inheritance. Lack of causal /disease‐contributing variants in 64% of GPP patients suggests a role for other, not yet identified genes. Genotype–phenotype correlation did not reveal significant correlations aside from the presence of IL36RN mutations with age at onset. What is the translational message? This study of three genes provides evidence that the inheritance of GPP is more complex than previously understood. The role of known genes in GPP is rather limited, as almost two‐thirds of patients do not carry a variant in any of these genes. In palmoplantar pustular psoriasis, the percentage of noncarriers is even lower. Further genetic studies will reveal the diseases' pathogenesis and provide a basis to use/develop more specific treatments. Linked Comment: Capon. Br J Dermatol 2018;178 :589–590 Respond to this article